Helicase antigen (HAGE)‐derived vaccines induce immunity to HAGE and ImmunoBody®‐HAGE DNA vaccine delays the growth and metastasis of HAGE‐expressing tumors in vivo. Issue 9 (19th September 2021) - Nagarajan, Divya; Pearson, Joshua; Brentville, Victoria; Metheringham, Rachael; Pockley, A Graham; Durrant, Lindy; McArdle, Stephanie E
Abstract: The management of patients with triple‐negative breast cancer (TNBC) continues to pose a significant clinical challenge. Less than 30% of women with metastatic TNBC survive 5 years, despite adjuvant chemotherapy and the initial higher rates of clinical response that can be achieved with neoadjuvant chemotherapy. ImmunoBody is a plasmid DNA designed to encode a human antibody molecule with complementarity‐determining regions engineered to express cytotoxic and helper T‐cell epitopes derived from the cancer antigen of interest. The helicase antigen (HAGE) is a cancer testis antigen, which is expressed in TNBC. Herein, we have identified a 30‐amino‐acid‐long HAGE‐derived sequence containing human leukocyte antigen (HLA)‐A2‐ and HLA‐DR1‐restricted epitopes and demonstrated that the use of this sequence as a peptide (with CpG/incomplete Freund's adjuvant) or incorporated into an ImmunoBody vaccine can generate specific interferon‐γ‐secreting splenocytes in HHDII + DR1 + mice. T‐cell responses elicited by the ImmunoBody‐HAGE vaccine were superior to peptide immunization. Moreover, splenocytes from ImmunoBody‐HAGE‐vaccinated mice stimulated in vitro could recognize HAGE + tumor cells and the human TNBC cell line MDA‐MB‐231. More importantly, the growth of implanted HHDII + DR1 + HAGE + Luc + B16 cells. Abstract : Less than 30% of triple‐negative breast cancer (TNBC) patients with metastasis survive after diagnosis, despite adjuvant chemotherapy and the initial higher rates of clinical response that can be achieved with neoadjuvant chemotherapy. Cancer vaccine‐based immunotherapy can induce protective, robust and sustained antitumor immunity against relevant target antigens. Helicase antigen (HAGE), a cancer testis antigen, is expressed by 43% of locally advanced primary TNBC. Here, we demonstrate the potential of HAGE‐derived vaccines for treating HAGE‐expressing cancers which could be considered as therapeutic options for patients with TNBC after conventional treatment to prevent disease recurrence.